Problem Solving Skills of Mathematics Education Students with Lack Number Sense Ability - Arjudin, Arjudin; Turmuzi, Muhammad; Kurniati, Nani; Wulandari, Nourma Pramestie (FKIP Universitas Lampung, 2024)
Abstract: Problem-solving in mathematics is a fundamental skill that must be mastered by individuals. However, previous research indicates that students' problem-solving abilities tend to be moderate to low. Many factors contribute to this, including the factor of number sense ability. The objective of this study is to describe how number sense and problem-solving skills are used by mathematics education students with low number sense ability in solving linear programming problems using the simplex method. This research is qualitative descriptive involving 36 third-year mathematics education students as participants. Subjects were selected using purposive sampling technique based on a number sense ability test to identify those with low number sense ability. Participants were given an advanced test involving linear programming problems solved using the simplex method. The results indicate that mathematics education students with low number sense ability struggle to solve problems accurately. Stages of problem-solving that were not performed effectively included gathering information, planning, and implementing the plan. Furthermore, students did not engage in the reviewing stage. Moreover, students were not flexible in manipulating numbers, especially when dealing with large numbers. As a result, more time was required for computations, and the iteration process in the simplex method could not be effectively completed. Keywords: linear programming, number sense, number sense ability, problem solving, simplex method.DOI: https://dx.doi.org/10.23960/jpmipa/v25i1.pp103-115